船载GT-sCO₂双布雷顿联合循环 经济分析与多目标优化 = Exergoeconomic analysis and multi-objective optimization of a marine GT-sCO₂ dual Brayton combined cycle - Wang, Qun (2024)
To further improve the efficiency of the gas turbine in shipboard power system and reduce energy consumption and costs, this paper analyzes and optimizes the thermal and economic performance of the gas turbine and supercritical carbon dioxide(GT-sCO2)dual Brayton combined cycle. Firstly, the exergetic and exergoeconomic analyses are conducted for the proposed system; then 6 decision variables are selected and their influence on the two objective functions(namely, exergetic efficiency and unit power cost)is studied; finally, a multi-objective optimization method based on non-dominated sorting genetic algorithm is used to optimize the combined cycle and obtain the optimal system parameters. The results show that under the design conditions, compared with the single gas turbine cycle, the GT-sCO2 combined cycle increases the net power by 29.44% and the exergetic efficiency by 29.21%, and decreases the unit power cost by 6.2%, showing obvious advantages in terms of both thermodynamic performance and economic performance. The sum of exergetic loss of all components thereof accounts for 31.66% of the total exergetic input, and the cost of exergetic loss accounts for 69.85% of the total cost. Thermal parameters of key components should be optimized to improve the exergoeconomic performance of the cycle. Parametric studies with variables controlled show that there are possible optimal exergetic efficiency and unit power cost by controlling the decision variables. Through multi-objective optimization, the optimal exergetic efficiency of the combined system is 48.44%, the optimal unit power cost is 0.292 6 yuan/(kW·h), and the net output power is 42 804 kW. This paper provides reference for the performance research on the combined cycle composed of the marine gas turbine cycle and waste heat recovery cycle from the perspective of thermal performance and economic performance.